(untitled) (Experimental biology, 2015)
Resistant and sensitive to lead and zinc genotypes are identified in the laboratory conditions. The genotype of Ming- 2 is characterized stability to lead. Most steady to the action of zinc was a genotype Мironovskaya 808. Sort of winter wheat Мironovskaya 808 showed most stability to the action of both metals.